Is Politically Correct a bit of a stretch? Some observations starting from Anna Maria Lorusso’s book "L’utilità del senso comune" - Sisca, Vittoria (Scenari, 2023)
The debate around political correctness is currently one of the predominant topics within the public discourse. More precisely, given that the conduct to which this term refers to has been a cause of social dispute since the 1980s, it would be more accurate to say that political correctness is an issue that has been inflaming the minds of the diverse and articulate fabric that is public opinion for about half a century. The aim of this review article is to sketch out a possible key to interpret this phenomenon, presenting the reader with the point of view expressed by the Italian semiologist Anna Maria Lorusso in her last book L’utilità del senso comune (2022).